Studying the Depth Structure of the Kyrgyz Tien Shan by Using the Seismic Tomography and Magnetotelluric Sounding Methods - Irina Medved; Elena Bataleva; Michael Buslov (Geosciences, 2021)
This paper presents new results of detailed seismic tomography (ST) on the deep structure beneath the Middle Tien Shan to a depth of 60 km. For a better understanding of the detected heterogeneities, the obtained velocity models were compared with the results of magnetotelluric sounding (MTS) along the Kekemeren and Naryn profiles, running parallel to the 74 and 76 meridians, respectively. We found that in the study region the velocity characteristics and geoelectric properties correlate with each other. The high-velocity high-resistivity anomalies correspond to the parts of the Tarim and Kazakhstan-Junggar plates submerged under the Tien Shan. We revealed that the structure of the Middle Tien Shan crust is conditioned by the presence of the Central Tien Shan microcontinent. It manifests itself as two anomalies lying one below the other: the lower low-velocity low-resistivity anomaly, and the upper high-velocity high-resistivity anomaly. The fault zones, limiting the Central Tien Shan microcontinent, appear as low-velocity low-resistivity anomalies. The obtained features indicate the fluid saturation of the fault zones. According to the revealed features of the Central Tien Shan geological structure, it is assumed that the lower-crustal low-velocity layer can play a significant role in the delamination of the mantle part of the submerged plates.